Commit 29a4f1e6 authored by Raphael CAUDERLIER's avatar Raphael CAUDERLIER

Girard paradox from Martin Löf 1972 paper

parent 4565cbd3
#NAME paradox.
(; This is a formulation by Per Martin-Löf of Girard Paradox. It comes
from pp. 7 to 9 of the 1972 presentation of MLTT.
Girard Paradox itself derives from Burali-Forti paradox, an older
paradox in set theory related to ordinals.
This paradox shows that Martin-Löf Type Theory is not consistent with
the assumption of an universe of all types V such that V : V.
Only a fragment of the inductive types defined in MLTT are actually
used. The paradox uses dependent products and sums, the empty type,
and natural numbers (to formalize the notion of infinite descending
chain). ;)
type : Type.
def term : type -> Type.
V : type.
[] term V --> type.
(; note that V : term V. ;)
Empty : Type.
empty : type.
[] term empty --> Empty.
pi : A : type -> (term A -> type) -> type.
[A,B] term (pi A B) --> a : term A -> term (B a).
Sig : A : type -> (term A -> type) -> Type.
sig : A : type -> (term A -> type) -> type.
[A,B] term (sig A B) --> Sig A B.
Pair : A : type -> B : (term A -> type) -> a : term A -> term (B a) -> Sig A B.
def fst : A : type -> B : (term A -> type) -> Sig A B -> term A.
[a] fst _ _ (Pair _ _ a _) --> a.
def snd : A : type -> B : (term A -> type) -> p : Sig A B -> term (B (fst A B p)).
[b] snd _ _ (Pair _ _ _ b) --> b.
N : Type.
n : type.
[] term n --> N.
O : N.
Succ : N -> N.
def Prod (A : type) (B : type) := Sig A (__ => B).
def prod (A : type) (B : type) := sig A (__ => B).
def arr (A : type) (B : type) := pi A (__ => B).
def Not (A : type) := term A -> Empty.
def not (A : type) := arr A empty.
(; Starting point of the formalisation of Girard Paradox ;)
(; From now on, we have only definitions and the last definition
inhabits the empty type.
The only exceptions to this rule are a pair of functions defined by
induction on natural numbers: gn and gn_increases. ;)
def rel (A : type) := arr A (arr A V).
def Rel (A : type) := term A -> term A -> type.
(; Transitivity ;)
def P (A : type) (lt : Rel A) :=
pi A (x : term A =>
pi A (y : term A =>
pi A (z : term A =>
arr (lt x y) (arr (lt y z) (lt x z))))).
(; No infinite descending chain. Remark that N is used here ;)
def Q (A : type) (lt : Rel A) :=
pi (arr n A) (f : (N -> term A) =>
not (pi n (n : N => lt (f (Succ n)) (f n)))).
def PQ (A : type) (lt : Rel A) := prod (P A lt) (Q A lt).
(; "Note that an ordering without descending chains is necessarily irreflexive" ;)
(; In fact, transitivity is not required here. ;)
def irrefl (A : type) (lt : Rel A) (q : term (Q A lt)) (a : term A) (H : term (lt a a)) : Empty :=
q (n : N => a) (n : N => H).
(; "U is the type of all orderings without infinite descending chains". ;)
def U_tail (A : type) := sig (rel A) (PQ A).
def U := sig V U_tail.
def mk_U (A : type) (ltA : Rel A) (pA : term (P A ltA)) (qA : term (Q A ltA)) : term U :=
Pair V U_tail A
(Pair (rel A) (PQ A) ltA
(Pair (P A ltA) (__ => Q A ltA) pA qA)).
(; First projection: carrier type ;)
def U_type : term U -> type := fst V U_tail.
def U_term (u : term U) := term (U_type u).
def U_arr (uA : term U) (uB : term U) := arr (U_type uA) (U_type uB).
def U_Arr (uA : term U) (uB : term U) := term (U_type uA) -> term (U_type uB).
def U_rel (u : term U) := rel (U_type u).
def U_Rel (u : term U) := Rel (U_type u).
def U_fst_tail := snd V U_tail.
(; Second projection: ordering relation ;)
def U_lt (u : term U) : U_Rel u := fst (U_rel u) (PQ (U_type u)) (U_fst_tail u).
def U_Lt (u : term U) (x : U_term u) (y : U_term u) := term (U_lt u x y).
def U_p (u : term U) := P (U_type u) (U_lt u).
def U_P (u : term U) := term (U_p u).
def U_snd_tail (u : term U) := snd (U_rel u) (PQ (U_type u)) (U_fst_tail u).
(; Third projection: proof of transitivity ;)
def U_getP (u : term U) : term (P (U_type u) (U_lt u)) :=
fst (P (U_type u) (U_lt u)) (__ => Q (U_type u) (U_lt u)) (U_snd_tail u).
(; Fourth projection: proof that there is no infinite descending chain ;)
def U_getQ (u : term U) : term (Q (U_type u) (U_lt u)) :=
snd (P (U_type u) (U_lt u)) (__ => Q (U_type u) (U_lt u)) (U_snd_tail u).
(; Proof of irreflexivity (this is not a projection) ;)
def irreflexive (u : term U) (a : U_term u) (H : U_Lt u a a) : Empty := irrefl (U_type u) (U_lt u) (U_getQ u) a H.
(; Definition of monotonicity for a function between two U-orderings ;)
def increases (uA : term U) (uB : term U)
(f : term (U_type uA) -> term (U_type uB)) :=
pi (U_type uA) (x : U_term uA =>
pi (U_type uA) (y : U_term uA =>
arr (U_lt uA x y) (U_lt uB (f x) (f y)))).
(; Definition of beeing a bound for such a function ;)
def bounded (uA : term U) (uB : term U)
(f : U_Arr uA uB)
(b : U_term uB) :=
pi (U_type uA) (x : U_term uA => U_lt uB (f x) b).
(; "On U we define a binary relation \lt_U" ;)
def ltU (uA : term U) (uB : term U) :=
sig (U_arr uA uB) (f : U_Arr uA uB =>
sig (U_type uB) (b : U_term uB =>
prod (increases uA uB f) (bounded uA uB f b))).
def LtU (uA : term U) (uB : term U) := term (ltU uA uB).
(; Constructor of LtU ;)
def mk_ltU (uA : term U) (uB : term U)
(f : U_Arr uA uB)
(b : U_term uB)
(morph : term (increases uA uB f))
(bound : term (bounded uA uB f b)) :=
Pair (U_arr uA uB)
(f : U_Arr uA uB =>
sig (U_type uB) (b : U_term uB =>
prod (increases uA uB f)
(bounded uA uB f b)))
f
(Pair (U_type uB) (b : U_term uB =>
prod (increases uA uB f)
(bounded uA uB f b))
b
(Pair (increases uA uB f)
(__ => bounded uA uB f b)
morph bound)).
(; First projection of LtU: the increasing function ;)
def ltU_fun (uA : term U) (uB : term U) (lt : LtU uA uB) : U_Arr uA uB :=
fst (U_arr uA uB) (f : U_Arr uA uB =>
sig (U_type uB) (b : U_term uB =>
prod (increases uA uB f)
(bounded uA uB f b))) lt.
def ltU_fst_tail (uA : term U) (uB : term U) (lt : LtU uA uB) :=
snd (U_arr uA uB) (f : U_Arr uA uB =>
sig (U_type uB) (b : U_term uB =>
prod (increases uA uB f)
(bounded uA uB f b))) lt.
(; Second projection of LtU: the bound ;)
def ltU_b (uA : term U) (uB : term U) (lt : LtU uA uB) : U_term uB :=
fst (U_type uB) (b : U_term uB =>
prod (increases uA uB (ltU_fun uA uB lt))
(bounded uA uB (ltU_fun uA uB lt) b))
(ltU_fst_tail uA uB lt).
def ltU_snd_tail (uA : term U) (uB : term U) (lt : LtU uA uB) :=
snd (U_type uB) (b : U_term uB =>
prod (increases uA uB (ltU_fun uA uB lt))
(bounded uA uB (ltU_fun uA uB lt) b))
(ltU_fst_tail uA uB lt).
(; Third projection of LtU: the proof of monotonicity ;)
def ltU_increases (uA : term U) (uB : term U) (lt : LtU uA uB) :=
fst (increases uA uB (ltU_fun uA uB lt)) (__ => bounded uA uB (ltU_fun uA uB lt) (ltU_b uA uB lt)) (ltU_snd_tail uA uB lt).
(; Fourth projection of LtU: the proof of bound ;)
def ltU_bounded (uA : term U) (uB : term U) (lt : LtU uA uB) :=
snd (increases uA uB (ltU_fun uA uB lt)) (__ : term (increases uA uB (ltU_fun uA uB lt)) => bounded uA uB (ltU_fun uA uB lt) (ltU_b uA uB lt)) (ltU_snd_tail uA uB lt).
(; Now we prove that LtU is transitive ;)
def transU_fun (uA : term U) (uB : term U) (uC : term U) (ltAB : LtU uA uB) (ltBC : LtU uB uC) (a : U_term uA) :=
ltU_fun uB uC ltBC (ltU_fun uA uB ltAB a).
def transU_increases (uA : term U) (uB : term U) (uC : term U) (ltAB : LtU uA uB) (ltBC : LtU uB uC) (x : U_term uA) (y : U_term uA) (H : U_Lt uA x y) : U_Lt uC (transU_fun uA uB uC ltAB ltBC x) (transU_fun uA uB uC ltAB ltBC y) :=
ltU_increases uB uC ltBC (ltU_fun uA uB ltAB x) (ltU_fun uA uB ltAB y) (ltU_increases uA uB ltAB x y H).
def transU_bounded (uA : term U) (uB : term U) (uC : term U) (ltAB : LtU uA uB) (ltBC : LtU uB uC) (x : U_term uA) : U_Lt uC (transU_fun uA uB uC ltAB ltBC x) (ltU_b uB uC ltBC) :=
ltU_bounded uB uC ltBC (ltU_fun uA uB ltAB x).
def transU : term (P U ltU) :=
uA : term U =>
uB : term U =>
uC : term U =>
ltAB : LtU uA uB =>
ltBC : LtU uB uC =>
mk_ltU uA uC (transU_fun uA uB uC ltAB ltBC) (ltU_b uB uC ltBC) (transU_increases uA uB uC ltAB ltBC) (transU_bounded uA uB uC ltAB ltBC).
(; Now we prove that LtU has no infinite descending chain. To do so,
we show that from an infinite descending chain F in U, we can build an
infinite descending chain hn in the first ordering. ;)
def tAn (F : N -> term U) (n : N) :=
U_type (F n).
def An (F : N -> term U) (n : N) :=
U_term (F n).
def ltn (F : N -> term U) (n : N) :=
U_lt (F n).
def pn (F : N -> term U) (n : N) :=
U_getP (F n).
def qn (F : N -> term U) (n : N) :=
U_getQ (F n).
def fn (F : N -> term U) (Hlt : n : N -> LtU (F (Succ n)) (F n)) (n : N) :=
ltU_fun (F (Succ n)) (F n) (Hlt n).
def an (F : N -> term U) (Hlt : n : N -> LtU (F (Succ n)) (F n)) (n : N) :=
ltU_b (F (Succ n)) (F n) (Hlt n).
(; We define gn := f_0 \circ f_1 ... \circ f_{n-1}. This function has no
name in Martin-Löf's formalisation. ;)
def gn : F : (N -> term U) -> (n : N -> LtU (F (Succ n)) (F n)) ->
n : N -> An F n -> An F O.
[F,Hlt,x] gn F Hlt O x --> x
[F,Hlt,n,x] gn F Hlt (Succ n) x --> gn F Hlt n (fn F Hlt n x).
def gn_increases : F : (N -> term U) ->
Hlt : (n : N -> LtU (F (Succ n)) (F n)) ->
n : N ->
term (increases (F n) (F O) (gn F Hlt n)).
[F,Hlt,x,y,H] gn_increases F Hlt O x y H --> H
[F,Hlt,n,x,y,H] gn_increases F Hlt (Succ n) x y H --> gn_increases F Hlt n (fn F Hlt n x) (fn F Hlt n y) (ltU_increases (F (Succ n)) (F n) (Hlt n) x y H).
(; We define hn := gn (an). ;)
def hn (F : N -> term U) (Hlt : n : N -> LtU (F (Succ n)) (F n)) (n : N) : An F O :=
gn F Hlt n (an F Hlt n).
(; We prove that hn is an infinite descending chain in A0. ;)
def hn_inf_desc (F : N -> term U) (Hlt : n : N -> LtU (F (Succ n)) (F n)) (n : N) :
term (ltn F O (hn F Hlt (Succ n)) (hn F Hlt n)) :=
(; We have to prove h_{n+1} <0 h_n,
that is by definition g_n (f_n(a_{n+1})) <0 g_n (a_n),
this holds by the fact that a_n is a bound and g_n is increasing ;)
gn_increases F Hlt n (fn F Hlt n (an F Hlt (Succ n)))
(an F Hlt n) (ltU_bounded (F (Succ n)) (F n) (Hlt n) (an F Hlt (Succ n))).
def no_inf_desc_chain_U : term (Q U ltU) :=
F : (N -> term U) =>
Hlt : (n : N -> LtU (F (Succ n)) (F n)) =>
qn F O (hn F Hlt) (hn_inf_desc F Hlt).
def U2 : term U := mk_U U ltU transU no_inf_desc_chain_U.
def U_gt (A : term U) (a : U_term A) (x : U_term A) := U_lt A x a.
def truncate (A : term U) (a : U_term A) : type :=
sig (U_type A) (U_gt A a).
def truncate_lt (A : term U) (a : U_term A) : Rel (truncate A a) :=
x : term (truncate A a) =>
y : term (truncate A a) =>
U_lt A (fst (U_type A) (U_gt A a) x) (fst (U_type A) (U_gt A a) y).
def truncate_p (A : term U) (a : U_term A) : term (P (truncate A a) (truncate_lt A a)) :=
x : term (truncate A a) =>
y : term (truncate A a) =>
z : term (truncate A a) =>
U_getP A
(fst (U_type A) (U_gt A a) x)
(fst (U_type A) (U_gt A a) y)
(fst (U_type A) (U_gt A a) z).
def truncate_q (A : term U) (a : U_term A) : term (Q (truncate A a) (truncate_lt A a)) :=
f : (N -> term (truncate A a)) =>
Hlt : (n : N -> term (truncate_lt A a (f (Succ n)) (f n))) =>
U_getQ A
(n : N => fst (U_type A) (U_gt A a) (f n))
Hlt.
def truncate_U (A : term U) (a : U_term A) : term U :=
mk_U (truncate A a) (truncate_lt A a) (truncate_p A a) (truncate_q A a).
def truncate_increases (A : term U) (a : U_term A) (b : U_term A) (H : U_Lt A a b) :
LtU (truncate_U A a) (truncate_U A b) :=
mk_ltU (truncate_U A a) (truncate_U A b)
(x : term (truncate A a) =>
Pair (U_type A) (U_gt A b)
(fst (U_type A) (U_gt A a) x)
(U_getP A (fst (U_type A) (U_gt A a) x) a b (snd (U_type A) (U_gt A a) x) H))
(Pair (U_type A) (U_gt A b) a H)
(x : term (truncate A a) =>
y : term (truncate A a) =>
H : term (truncate_lt A a x y) => H)
(snd (U_type A) (U_gt A a)).
def truncate_bounded (A : term U) (a : U_term A) : LtU (truncate_U A a) A :=
mk_ltU (truncate_U A a) A
(fst (U_type A) (U_gt A a))
a
(x : term (truncate A a) =>
y : term (truncate A a) =>
H : term (truncate_lt A a x y) => H)
(snd (U_type A) (U_gt A a)).
def U2_max (A : term U) : LtU A U2 :=
mk_ltU A U2
(truncate_U A)
A
(truncate_increases A)
(truncate_bounded A).
def contradiction : Empty :=
irreflexive U2 U2 (U2_max U2).
Markdown is supported
0% or
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment